ANALYSIS OF THE EFFECT OF PROMOTION FOCUS VARIABLES AND PREVENTION FOCUS ON IMPULSE BUYING TENDENCY VARIABLES: EMPIRICAL STUDY ON SHOPEE: ANALISIS PENGARUH VARIABEL FOKUS PROMOSI DAN FOKUS PENCEGAHAN TERHADAP VARIABEL IMPULSE BUYING TENDENCY: STUDI EMPIRIS PADA SHOPEE - Arijaya, Vincentius Edbert; S.E., M.M, Dr. Teofilus (PERFORMA, 2022)
Impulse buying is a very complex behavior exhibited by retail consumers and so many components - components that can affect both externally and internally. Previous researchers have observed that consumer emotions and focus play an important role in increasing impulsivity, which leads to impulse buying tendencies in the retail world. An interesting phenomenon from this research is the tendency of this impulse buying to shift from offline but now online as well. Where currently e-commerce is competing to understand the regulators of consumer focus and emotions to lead to impulse buying tendencies. Therefore, this study aims to examine the influence of each individual's focus regulator on the influence of impulse buying tendencies and to see the moderating effect of emotions on the world of e-commerce. This study uses SPSS Statistics with validity, reliability, classical assumption tests (normality, multicollinearity, heteroscedasticity), hypothesis testing (R2 test, F test, t test), and Moderated Multiple Regression (MMR) analysis. The sample used is shopee users in Surabaya as many as 153 respondents but only 140 respondents who fit the existing prerequisites. The results of this study show that individuals with a promotion focus have an effect on impulsive buying tendencies, but on the contrary with a prevention focus, which shows a person with a prevention focus has no effect on impulsive buying tendencies. In the moderated case using emotions, it shows a different effect where emotions cause someone with a promotional focus individual to show a weaker influence on the impulse buying tendency, while in an individual with a prevention focus it shows that emotion has no effect on preventing impulsive buying tendencies but can actually help an prevention individual to make impulse buying tendencies.